Die militärpolitische Emanzipation Deutschlands – Afrika als Exerzierplatz? - Ruf, Werner (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2011)
After World War II (West-)Germany was supposed to never again become a military Power. When it joined NATO all its troops had to be under the command of the alliance – but its contributions to NATO grew steadily. In the 2 + 4 treaty the united Germany pledged to never undertake any military aggression. With the Treaty of Masstricht the EU started to establish its own security policy. Germany’s active engagement in both alliances became its instrument for military emancipation. With growing military engagement of the EU (and Germany) – especially in Africa – as well as the predominant role of Germany in the EU and its engagement in the UN and NATO, the country is back on its way to becoming one of the big powers.